Agenda 2007: The first stage of financial negotiations in Europe 2007-2013 - Peter Becker (Stiftung Wissenschaft und Politik (SWP), 2004)
The successful conclusion to the Intergovernmental Conference on the European Constitutional Treaty means that negotiations on the next financial framework for the enlarged European Union - the Financial Perspective or Agenda 2007 - constitute the next major area of discussion within the EU. These financial negotiations will set the Union's political priorities for the years 2007 to 2013. On 14 July 2004 the European Commission presented a package of detailed draft legislation specifying the communication published in February 2004 on the key issues of the future and the financial basis of the Union's policies. The new package contains proposals for Regulations on Europe's future cohesion, structural and agricultural policy, two proposals on the reform of the European own resources system, and a draft version of a reformed interinstitutional agreement between the Council, Parliament and the Commission. (SWP Comments / SWP)
Keywords: 320